Eksplorasi Peran Tourism Satisfaction dalam Memediasi Hubungan Antara E-Wom, Destination Image dan Tourism Loyalty (Studi Kasus Wisata Air Terjun Moramo Sulawesi Tenggara) - Hamid, Nisrina; Swastika, Yuan; Wulansari, Wiwin Putri (J-MAS (Jurnal Manajemen dan Sains), 2024)
Electronic Word of Mouth (E-WoM) and destination image play a significant role in the tourism sector and have a strong influence on tourism satisfaction and tourism loyalty. This research aims to understand and identify the implications of E-WoM and destination image on tourism loyalty and tourism satisfaction as mediating (intervening) variables in Moramo Waterfall Tourism, Southeast Sulawesi. The analytical approach used is to use the SEM-PLS analysis tool with a sample of 160 respondents using purposive sampling. The results of the study show that the E-Wom and destination image variables have a positive and significant effect on tourism satisfaction and tourism loyalty. The more positive information and reviews and the more positive the image of the Moramo Waterfall tourist attraction in Southeast Sulawesi, the higher the tourism satisfaction and the stronger the formation of tourism loyalty, therefore tourism satisfaction is an important strategy to build tourism loyalty and the influence of both variables is positive and significant. The results of the study also show that tourism satisfaction as a mediating variable has a positive and significant effect on tourism loyalty, although the mediating effect is low.